Advances in Virtual, Augmented, and Mixed Reality Technologies. Issue 5 (1st September 2018) - Bhowmik, Achintya K.
Abstract : Virtual, augmented, and mixed reality (VR/AR/MR) technologies offer the promise of seamlessly blending the real and the virtual worlds, thereby enabling many exciting immersive and interactive applications and experiences. This article provides a synopsis of some of the key new developments in the field presented at Display Week 2018.